The Orapuh Review System: How to initiate and conduct an Orapuh Review - Adamu, V. E. (Orapuh Journal, 2022)
An Orapuh Review is a standalone survey of current scholarly sources on a specific oral and/or public health topic to provide an (updated) overview of knowledge in that area. An Orapuh Review involves 17 steps from Conception to the final published product. The 17 steps are grouped into 3 major stages: preparation, review, and production. Writing an Orapuh Review involves finding relevant publications (such as books and journal articles), critically analysing them, and explaining what you found. A good Orapuh Review doesn’t just summarize sources – it analyses, synthesizes, and critically evaluates to give a clear picture of the state of knowledge on the subject matter.